Предмет: Алгебра,
автор: TigerTM
Решите уравнение: (x^2-2x)^2 + (x-1)^2=1
Ответы
Автор ответа:
0
=x^4 - 2*2x*x^2 + 4x^2 + x^2 - 2x + 1 - 1 = 0
x^4 - 4x^3 + 5x^2 - 2x= 0
x( x^3 - 4x^2 + 5x -2) = 0
x=0 x^3 - 4x^2 + 5x -2 =0
решим по теореме горнера
-2: -+1 ; +-2
x=0, x= 1
x^2 - 3x + 2 =0
D = 9 -4*2=1
x1 = 3+1/2 = 2
x2 = 3-1/2 = 1
Ответ: x=0, x=1, x=2
Автор ответа:
0
x^4 - 2*2x*x^2 + 4x^2 + x^2 - 2x + 1 - 1 = 0
x^4 - 4x^3 + 5x^2 - 2x= 0
x( x^3 - 4x^2 + 5x -2) = 0
x=0 x^3 - 4x^2 + 5x -2 =0
решим по теореме горнера
-2: -+1 ; +-2
x=0, x= 1
x^2 - 3x + 2 =0
D = 9 -4*2=1
x1 = 3+1/2 = 2
x2 = 3-1/2 = 1
Ответ: x=0, x=1, x=2
Похожие вопросы
Предмет: Математика,
автор: igorpoliakov220408
Предмет: Английский язык,
автор: kadyralievnakenze
Предмет: История,
автор: evangelina97
Предмет: История,
автор: Nastya2210